The enigma and challenges of vitiligo pathophysiology and treatment. (12th April 2020) - Abdel‐Malek, Zalfa A.; Jordan, Christian; Ho, Tina; Upadhyay, Parth Rajendrakumar; Fleischer, Alan; Hamzavi, Iltefat
Abstract: Vitiligo is the most common acquired pigmentary disorder, which afflicts 0.5%–1% of the world population, and is characterized by depigmented skin patches resulting from melanocyte loss. Vitiligo has a complex etiology and varies in its manifestations, progression, and response to treatment. It presents as an autoimmune disease, evidenced by circulating melanocyte‐specific antibodies, and association with other autoimmune diseases. However, autoimmunity may be secondary to the high oxidative stress in vitiligo skin and to intrinsic defects in melanocytes and their microenvironment, which contribute to aberrant stress response, neo‐antigenicity, and susceptibility of melanocytes to immune attack and apoptosis. There is also a genetic predisposition to vitiligo, which sensitizes melanocytes to environmental agents, such as phenolic compounds. Currently, there are different treatment modalities for re‐pigmenting vitiligo skin. However, when repigmentation is achieved, the major challenge is maintaining the pigmentation, which is lost in 40% of cases. In this review, we present an overview of the clinical aspects of vitiligo, its pathophysiology, the intrinsic defects in melanocytes and their microenvironment, and treatment strategies. Based on lessons from the biology of human melanocytes, we present our perspective of how repigmentation of vitiligo skin can be achieved and sustained.